Effect of desensitizing toothpastes on dentine hypersensitivity: A systematic review and meta-analysis. (August 2018) - Hu, Meng-Long; Zheng, Gang; Zhang, You-Dong; Yan, Xiang; Li, Xiao-Chan; Lin, Hong
Abstract: Objectives: To evaluate the desensitizing effect of toothpastes that contain ingredients that act against dentine hypersensitivity (DH) and to compare this effect with negative controls. Sources: Five databases were searched to identify relevant articles published up to November 27, 2017. Study selection: Randomized controlled trials (RCTs) comparing desensitizing toothpastes with a toothpastes without desensitizing component in adult patients that suffer from DH were included. The risk of bias was assessed according to the Cochrane guidelines, and the quality of the evidence was evaluated using the GRADE tool. Inverse variance random-effects meta-analyses of standardized mean differences (SMD) and 95% confidence intervals (CIs) were calculated using RevMan 5.3 software. Data: 53 RCTs with 4796 patients were finally included in the meta-analysis. The toothpastes that contain active desensitization ingredients showed a better desensitizing effect on DH than the negative control, except the strontium- and amorphous calcium phosphate-containing toothpastes. The amorphous calcium phosphate–containing toothpaste had very low-quality evidence, the strontium, potassium and strontium, and potassium and stannous fluoride–containing toothpastes had low-quality evidence, and the other five toothpastes had moderate quality evidence. Conclusions: Our result support the premise that toothpastes containing potassium, stannous fluoride, potassium and strontium, potassium and stannous fluoride, calcium sodium phosphosilicate, arginine, and nano-hydroxyapatite relieve the symptoms of DH, but does not advise the use of toothpastes that contain strontium and amorphous calcium phosphate. Furthermore, high-quality studies are needed to confirm our results. (PROSPERO CRD42018085639)